DOMAIN SLEEP QUALITY IN END STAGE RENAL DISEASE PATIENTS UNDERGOING HEMODIALYSIS AT HOSPITAL DR. BRATANATA JAMBI - Wahyuni, Tri (Jurnal Ilmu-Ilmu Kesehatan, 2024)
This study aims to describe the sleep quality of ESRD undergoing hemodialysis at dr. Bratanata Jambi. The design of this research is descriptive. The results showed that the characteristics of ESRD undergoing hemodialysis were mostly female (61.10%), low maternal education level (58.35%), average length of hemodialysis 3.72±1.17, average age 53.33 ± 4.35 and the sleep quality of ESRD patients categorically shows that sleep quality is still poor that the frequency distribution of respondents has quite poor sleep quality as much as 63.90%, respondents with a sleep latency of 31-60 minutes as much as 80.60%, respondents who have a sleep duration of 6-7 hours as much as 72.2%, respondents who have sleep efficiency of 65-74% as much as 80.60%, respondents who have sleep disorders 1-2 times a week as much as 100%, respondents who never use drugs sleep 88.90% and respondents who have dysfunctional activities during the day 1x a week as much as 91.70%. Conclusion Based on research conducted by researchers, categorically, poor sleep quality is caused by long sleep duration, short sleep duration and sleep disturbances such as building the bathroom, overheating at night and insomnia. It is hoped that nurses can provide appropriate complementary interventions or therapies for ESRD patients undergoing hemodialysis on how to improve sleep quality in ESRD patients undergoing hemodialysis. Keywords: Hemodialysis, sleep quality, HD duration, education, age.